The influence of corporate governance towards capital structure; Quality of Financial Reporting as mediating variabel - Sinta Devita; Abel Tasman (Universitas Negeri Padang, 2021)
This research analized the influence of mediating the variable quality of financial reports on the relationship between corporate governance and capital structure. The object of this study is all manufacturing companies listed on the IDX in 2014-2018. The sample in this study was conducted by purposive sampling. This study uses SPSS version 24 path analysis. The results show that Corporate Governance has a significant effect on Capital Structure. Corporate Governance has a significant effect on the Quality of Financial Reporting, whereas the Quality of Financial Reporting has no significant effect on Capital Structure and the Quality of Financial Reporting does not mediate the effect of Corporate Governance on the capital Structure.